Car Air Conditioner System Simulator Design for Student Practicum - Nuzul Hidayat; M Giatman; Mukhlidi Muskhir; Hansi Effendi; Ahmad Arif (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
This research aims to develop a car air conditioning (AC) simulator. The vehicle's air conditioning system is transferred to a stand panel with an electric motor drive. The selection of an electric motor simplifies operation, maintenance, and practicality because the AC system does not require much time to warm up. The rotation of the electric motor is regulated by an inverter so that the performance of the AC system matches the actual performance. The R and D approach was selected for this investigation. The technique begins with examining an existing simulator, followed by planning, creating, expert validation, and completion of the simulator. The expert validation of the material's feasibility yielded a score of 3.73 with a highly feasible category, a score of 3.45 with a viable category for media, and a score of 3.20 with a feasible category for efficacy. It has been demonstrated that, on average, there is a 36.18 percent improvement in comprehension when this technique is utilized. Tujuan penelitian ini adalah membuat simulator air conditioner (AC) mobil dengan cara memindahkan sistem AC dari mobil ke panel stand dengan penggerak motor listrik. Pemilihan motor listrik adalah untuk mempermudah pengoperasian, perawatan serta kepraktisan karena tidak butuh waktu yang lama untuk pemanasan sistem AC. Sebuah inverter digunakan sebagai pengatur putaran motor listrik, sehingga kinerja sistem AC sesuai dengan kinerja sebenarnya. Metode R and D dipilih dalam penelitian ini. Metode diawali dengan mengamati simulator yang sudah ada, merencanakan, mengembangkan, melakukan validasi simulator oleh ahli, dan finalisasi simulator. Hasil validasi ahli untuk kelayakan materi memperoleh nilai nilai 3.73 dengan kategori sangat layak, untuk media memperoleh nilai 3.45 dengan kategori layak, serta untuk keefektifan dengan nilai 3.20 dengan kategori layak. Pada saat digunakan, terbukti ada kenaikan pemahaman dengan rerata 36.18%.